1991
DOI: 10.1007/bf02388121
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and measurement of confluency of rabbit primary proximal tubule kidney cells grown on millicell-HA membrane filters

Abstract: SUMMARY:We have characterized primary rabbit kidney proximal tubule cells grown on Millipore cellulose fihers (Millicell-HA) in which the cells are exposed to culture medium on both the apical and basolateral sides. Cells reach confluency 12 to 14 d after plating. Methods are described for removal of the cells from the filters and measurement of the integrity of the monolayer at confluency by exclusion of [laC]inulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

1994
1994
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
2
Order By: Relevance
“…Thus, these cultures maintain tight junctions and active transepithelial transport function for extended periods without the use of a collagen substrate. In contrast, Ford et al (20) and Palmoski et al (21) reported that primary cultures of rabbit RPT cells seeded at 4 mg/membrane, a density approximately fourfold higher than that used in this study, and grown on 30-mm Millicell-HA filters without collagen required 10 to 12 d to reach confluence. The basal-to-apical transepithelial flux of PAH in these cultures was reduced only 55% during a 20-min coincubation with probenecid (21).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Thus, these cultures maintain tight junctions and active transepithelial transport function for extended periods without the use of a collagen substrate. In contrast, Ford et al (20) and Palmoski et al (21) reported that primary cultures of rabbit RPT cells seeded at 4 mg/membrane, a density approximately fourfold higher than that used in this study, and grown on 30-mm Millicell-HA filters without collagen required 10 to 12 d to reach confluence. The basal-to-apical transepithelial flux of PAH in these cultures was reduced only 55% during a 20-min coincubation with probenecid (21).…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast, Ford et al (20) and Palmoski et al (21) reported that primary cultures of rabbit RPT cells seeded at 4 mg/membrane, a density approximately fourfold higher than that used in this study, and grown on 30-mm Millicell-HA filters without collagen required 10 to 12 d to reach confluence. The basal-to-apical transepithelial flux of PAH in these cultures was reduced only 55% during a 20-min coincubation with probenecid (21). Thus, in contrast to previous studies, the cultures grown under the conditions described in the present study reached confluence more quickly and maintained carrier-mediated organic anion transport for extended periods.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation